H migration in peroxy radicals under atmospheric conditions - L. Vereecken; L. Vereecken; L. Vereecken; B. Nozière (Atmospheric Chemistry and Physics, 2020)
A large data set of rate coefficients for H migration in peroxy radicals is presented and supplemented with literature data to derive a structure–activity relationship (SAR) for the title reaction class. The SAR supports aliphatic RO2 radicals; unsaturated bonds and β-oxo substitutions both endocyclic and exocyclic to the transition state ring; and α-oxo (aldehyde), –OH, –OOH, and –ONO2 substitutions, including migration of O-based hydrogen atoms. Also discussed are –C( = O)OH and –OR substitutions. The SAR allows predictions of rate coefficients k(T) for a temperature range of 200 to 450 K, with migrations spans ranging from 1,4 to 1,9-H shifts depending on the functionalities. The performance of the SAR reflects the uncertainty of the underlying data, reproducing the scarce experimental data on average to a factor of 2 and the wide range of theoretical data to a factor of 10 to 100, depending also on the quality of the data. The SAR evaluation discusses the performance in multi-functionalized species. For aliphatic RO2, we also present some experimental product identification that validates the expected mechanisms. The proposed SAR is a valuable tool for mechanism development and experimental design and guides future theoretical work, which should allow for rapid improvements of the SAR in the future. Relative multi-conformer transition state theory (rel-MC-TST) kinetic theory is introduced as an aid for systematic kinetic studies.